Attributes of clinical guidelines that influence use of guidelines in general practice: observational study - Grol, Richard (British Medical Journal, 1998)
Objective: To determine which attributes of clinical practice guidelines influence the use of guidelines in decision making in clinical practice. Design: Observational study relating the use of 47 different recommendations from 10 national clinical guidelines to 12 different attributes of clinical guidelines—for example, evidence based, controversial, concrete. Setting: General practice in the Netherlands. Subjects: 61 general practitioners who made 12 880 decisions in their contacts with patients. Main outcome measures: Compliance of decisions with clinical guidelines according to the attribute of the guideline. Results: Recommendations were followed in, on average, 61% (7915/12 880) of the decisions. Controversial recommendations were followed in 35% (886/2497) of decisions and non-controversial recommendations in 68% (7029/10 383) of decisions. Vague and non-specific recommendations were followed in 36% (826/2280) of decisions and clear recommendations in 67% (7089/10 600) of decisions. Recommendations that demanded a change in existing practice routines were followed in 44% (1278/2912) of decisions and those that did not in 67% (6637/9968) of decisions. Evidence based recommendations were used more than recommendations for practice that were not based on research evidence (71% (2745/3841) v 57% (5170/9039)). Conclusions: People and organisations setting evidence based clinical practice guidelines should take into account some of the other important attributes of effective recommendations for clinical practice.